EMPOWERMENT OF WOMEN THROUGH AYURVEDA (AYURVEDA- A RAY OF LIGHT FOR THE WOMEN TRAPPED BETWEEN TRADITION AND MODERNITY) - Arora, Nishi; Srivastava, Nidhi (International Journal of Research -GRANTHAALAYAH, 2017)
Woman is the centre of any social system. She plays many roles in her life but it is strange, that she has to fight for each single moment for her survival. Time has changed the situation for women on the basis of official recognition but in reality, there are still many persistent conflicts hanging on a thin strand with similar strength to that of a hair.